Conditions of practice in perceptual skill learning - Memmert, D.; Hagemann, N.; Althoetmar, R.; Geppert, S.; Seiler, D. (Research Quarterly for Exercise and Sport, 2009)
This study uses three experiments with different kinds of training conditions to investigate the "easy-to-hard" principle, context interference conditions, and feedback effects for learning anticipatory skills in badminton. Experiment 1 (N = 60) showed that a training program that gradually increases the difficulty level has no advantage over the randomized variant. Experiment 2 (N = 60) pointed out that when comparing the blocked (lateral before depth dimension) perceptual training group with the random perceptual training group a significant advantage for the random group was found in the retention test (depth error). Experiment 3 (N = 40) demonstrated that training with reduced feedback (66 %) is no more effective than 100% feedback training in a group of novice performers.